RNA-binding proteins in vascular inflammation and atherosclerosis - Sachse, Marco; Tual-Chalot, Simon; Ciliberti, Giorgia; Amponsah-Offeh, Michael; Stamatelopoulos, Kimon; Gatsiou, Aikaterini; Stellos, Konstantinos (Atherosclerosis, 2023)
Atherosclerotic cardiovascular disease (ASCVD) remains the major cause of premature death and disability worldwide, even when patients with an established manifestation of atherosclerotic heart disease are optimally treated according to the clinical guidelines. Apart from the epigenetic control of transcription of the genetic information to messenger RNAs (mRNAs), gene expression is tightly controlled at the post-transcriptional level before the initiation of translation. Although mRNAs are traditionally perceived as the messenger molecules that bring genetic information from the nuclear DNA to the cytoplasmic ribosomes for protein synthesis, emerging evidence suggests that processes controlling RNA metabolism, driven by RNA-binding proteins (RBPs), affect cellular function in health and disease. Over the recent years, vascular endothelial cell, smooth muscle cell and immune cell RBPs have emerged as key co- or post-transcriptional regulators of several genes related to vascular inflammation and atherosclerosis. In this review, we provide an overview of cell-specific function of RNA-binding proteins involved in all stages of ASCVD and how this knowledge may be used for the development of novel precision medicine therapeutics.